2012
DOI: 10.1371/journal.pone.0038556
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with the Performance of a Blood-Based Interferon-γ Release Assay in Diagnosing Tuberculosis

Abstract: Background Indeterminate results are a recognised limitation of interferon - γ release assays (IGRA) in the diagnosis of latent tuberculosis (TB) infection (LTBI) and TB disease, especially in children. We investigated whether age and common co-morbidities were associated with IGRA performance in an unselected cohort of resettled refugees. Methods A retrospective cross-sectional study of refugees presenting for their post-resettlement health a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
44
1
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 39 publications
3
44
1
3
Order By: Relevance
“…The clear majority of indeterminate results occurred due to insufficient interferon gamma production in response to stimulation with PHA, which is consistent with data from other studies (10)(11)(12). Our results show that there is a significant relationship between age and PHA-induced interferon gamma responses, with an increasing trend in the first few years of life and a decreasing trend during adult life, likely reflecting immune maturation and subsequent immunosenescence.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…The clear majority of indeterminate results occurred due to insufficient interferon gamma production in response to stimulation with PHA, which is consistent with data from other studies (10)(11)(12). Our results show that there is a significant relationship between age and PHA-induced interferon gamma responses, with an increasing trend in the first few years of life and a decreasing trend during adult life, likely reflecting immune maturation and subsequent immunosenescence.…”
supporting
confidence: 91%
“…Previous publications, including our own, have shown that indeterminate QFT-GIT results occur in a considerable proportion of children evaluated for TB infection (5,9,10). However, few publications have specifically focused on indeterminate results in adults, and even fewer have included a comparison of the performance of QFT-GIT assays between pediatric and adult patients (11,12).…”
mentioning
confidence: 99%
“…10 Although we found decreased IFN-γ responsiveness to mitogen stimulation during acute malaria infections, the majority of the malaria patients responded well above the cutoff for positive mitogen response, and we were unable to demonstrate a direct effect on the QFT test. However, we did find an increased IP-10 indeterminate rate.…”
Section: Discussioncontrasting
confidence: 63%
“…1 A series of immunosuppressive conditions are known to compromise the IGRA test performance including human immunodeficiency virus (HIV) infection and low CD4 cell count, [2][3][4][5] glucocorticoid treatment, 6 cigarette smoking, 7 severe disease in children, 8 and helminth infection. 9,10 So far, no systematic evaluation of the possible effect of malaria infection on IGRA test performance has been done.…”
Section: Introductionmentioning
confidence: 99%
“…(MTB) could be used to diagnose the absence of TB infection in the body. 18 The immune system of children can be measured by the intake status related to the nutrition status of children. Even though the relevance of chronic disease exposure such as pulmonary TB that had directly affects children's nutrition status, predicting it as the measuring association is still difficult.…”
Section: Discussionmentioning
confidence: 99%